Secular Building (“The Bath-House”) in Pereyaslavl’ and the Residences of the Russian Hierarchs in the 11th–14th Centuries - Freze, Anna A. (Actual Problems of Theory and History of Art, 2019)
According to the Russian chronicles, metropolitan Ephrem initiated an intensive building program in the city of Pereyaslavl’ in the last quarter of the 11th century. Besides the cathedral, the chronicles mention stone walls, a gate with a church over it, a church near this gate, a bath-house and “other buildings”. This building program indicates that Ephrem of Pereyaslavl’ intended to erect an official residence for the metropolitans/bishops of the princedom. It is highly likely that the bath-house project was inspired byEphrem’s experience as a monk of an unknown Constantinopolitan monastery. The typika of the monasteriesin the Byzantine capital testify that it was the very time of the rising concern with the hygiene issues within the monastic society. It has been tentatively proposed that the civil building of the 11th century within the fortress of Pereyaslavl’ might be identified as Ephrem’s bath-house. This monument is in a poor state of preservation; however, the archaeologists were able to find six pieces of ceramic tubes, along with the fragments of elaborate décor of the building. The studied bath-houses of the middle Byzantine period throughout all EasternChristian countries demonstrate uniformity and consistency of their layouts. They are hardly matched with the civil building in Pereyaslavl’. Ceramic tubes being put aside, there is no archaeological evidence in favor of its functioning as a bath-house. Therefore, for today this secular building should be considered as a part of the palatial complex of the metropolitan. The study of this ensemble should be continued, being a key issue for understanding the first stage of evolution of the ecclesiastical residences in Old Rus’.